2019
DOI: 10.1016/j.future.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Community heuristics for user interface evaluation of crowdsourcing platforms

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…They can accommodate the participants' listings, realise their agreements, enable incentives, participation and value creation while they obtain commission for their services (Ford et al, 2015;Marjanovic et al, 2012;Taylor and Joshi, 2019;Zogaj et al, 2014). The extent to which the platforms provide a conducive space for communication within the value-creation process defines how much platforms shift towards the community side ( a Campo et al, 2019).…”
Section: Operational 431 Platforms Platforms Facilitating Value Creation As Solver Brokeragesmentioning
confidence: 99%
“…They can accommodate the participants' listings, realise their agreements, enable incentives, participation and value creation while they obtain commission for their services (Ford et al, 2015;Marjanovic et al, 2012;Taylor and Joshi, 2019;Zogaj et al, 2014). The extent to which the platforms provide a conducive space for communication within the value-creation process defines how much platforms shift towards the community side ( a Campo et al, 2019).…”
Section: Operational 431 Platforms Platforms Facilitating Value Creation As Solver Brokeragesmentioning
confidence: 99%
“…Ultimately, ineffective reputation system leads to dissatisfaction and a reduction in productivity [22]. Recommendation system aims to understand solver interests and preferences, and matches suitable crowdsourcing tasks with a specific solver [1]. Therefore, personalized recommendation system would save time for solvers and increase solver satisfaction and loyalty.…”
Section: Reverse Quality Attribute (R)mentioning
confidence: 99%
“…Wen and Lin [52] constructed an optimal fees structure of a crowdsourcing platform depending on the game-theoretic model. Veloso et al [51] used blockchain technology to construct a trust and reputation modelling to solve the problem of false data.à Campo et al [1] presented that heuristics can be used as a tool for designers of crowdsourcing platforms. Liang et al [34] confirmed that IT-enabled monitoring system reduces solver preference for high-reputable bidders and reputation premiums.…”
mentioning
confidence: 99%
“…Users should have the option to give the application feedback on what can be better or improved. It is crucial to know the needs of the users to satisfy them [69,70].…”
Section: Motivation and Retentionmentioning
confidence: 99%